Business model innovation through the lens of time: An empirical study of performance implications across venture life cycles - Elena Freisinger; Sven Heidenreich; Christian Landau; Patrick Spieth (Schmalenbach Journal of Business Research (SBUR), 2021)
Current literature suggests that the innovation of a business model is among the most important success factors for organizations and has a positive influence on their performance. What is not yet clear, however, is how this relationship unfolds during an organization's life cycle. We posit that business model innovation strongly contributes to firm performance in earlier phases, but ultimately gets less important. We therefore collected data on 250~organizations in Germany and used structural equation modeling for analytical purposes. We make the following two main contributions to the literature: (1)~We confirm recent findings about the positive impact of business model innovation on performance; (2)~we provide first empirical evidence for the important role of life cycle stages as moderator with regard to this relationship. With respect to the latter, our findings show that business model innovation is an important pathway of organizations, especially in their early years of existence, yet somewhat diminishing over time. In conclusion, this study opens new research avenues by extending and incorporating explanations for the life cycle theory and business model innovation.
Keywords: 650; Life cycle stages; Business model; Business model innovation; Firm performance